2014
DOI: 10.1007/s00408-014-9590-9
|View full text |Cite
|
Sign up to set email alerts
|

CT Quantification of Large Opacities and Emphysema in Silicosis: Correlations among Clinical, Functional, and Radiological Parameters

Abstract: The PFT findings were correlated with the EV, EI, LD, and LD%, but they were not correlated with the large opacities volume. These results suggest that the emphysema volume, more than the large opacities volume, is responsible for functional impairment in patients with complicated silicosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…Studies showed that the operators of sand blasters and stone cutting systems can be subjected to fine silica particulates which can lead to silicosis and lung cancer, both deadly lung diseases [20,21]. If the fracture behavior of particles during impact loading and materials processing was better understood, predictions of the dust generated during these processes might be used to limit worker exposure to harmful particulate matter.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that the operators of sand blasters and stone cutting systems can be subjected to fine silica particulates which can lead to silicosis and lung cancer, both deadly lung diseases [20,21]. If the fracture behavior of particles during impact loading and materials processing was better understood, predictions of the dust generated during these processes might be used to limit worker exposure to harmful particulate matter.…”
Section: Introductionmentioning
confidence: 99%
“…Traction on adjacent parenchyma may lead to associated paracicatricial emphysema. The emphysematous changes may be more important in lung function decline than the size of the PMF lesion . Importantly, however, symptomatology is not necessarily clearly related to radiological findings, especially in young workers.…”
Section: Patterns Of Diseasementioning
confidence: 98%
“…Such a technical feature has opened new avenues for the investigation of lung diseases. Objective measurements of the total pulmonary volume and of the volume of the lung affected by emphysema can be performed with high accuracy (27-36) .…”
Section: Commentsmentioning
confidence: 99%